A study on the demand of spatial planning and decision support system in Malaysia - Abdullah, Muhammad Faris; Abdullah, Alias; Ibrahim, Mansor; Abdul Samad, Dazilah (Malaysian Institute of Planners, 2005)
This paper examines the demand and interest for SPDSS (Spatial Planning and Decision Support System) among town planners in Malaysia. A survey was conducted among town planners registered with the Malaysian Institute of Planners and among local planning authorities. Based on the survey and analysis, it was revealed that many town planners in Malaysia are still unfamiliar with SPDSS, particularly the concept and its applications. Nevertheless, they have expressed interest to know more about SPDSS as well as to include SPDSS in their professional works.